2020
DOI: 10.18632/aging.103100
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 correlated with immune infiltration serves as a prognostic biomarker in endometrial carcinoma and renal papillary cell carcinoma: implication for COVID-19

Abstract: Angiotensin-converting enzyme 2 (ACE2) is a member of the renin-angiotension system, however, the correlation between ACE2 and prognosis in UCEC (Uterine Corpus Endometrial Carcinoma) and KIRP (Kidney Renal Papillary Cell Carcinoma) is not clear. We analyzed the expression levels of ACE2 in the Oncomine and TIMER databases, the correlation between ACE2 and overall survival in the PrognoScan, GEPIA and Kaplan-Meier plotter databases. The correlation between ACE2 and immune infiltration level and the type marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 39 publications
4
105
0
2
Order By: Relevance
“…In particular, the ACE2 downregulation correlates with worse survival and tumor advancement in KIRC, also known as clear cell renal cell carcinoma (ccRCC). Previous studies demonstrated that ACE2 exerts antitumor effects by inhibiting tumor angiogenesis [10] and promoting tumor immune in ltration [14]. Our results are consistent with these previous ndings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In particular, the ACE2 downregulation correlates with worse survival and tumor advancement in KIRC, also known as clear cell renal cell carcinoma (ccRCC). Previous studies demonstrated that ACE2 exerts antitumor effects by inhibiting tumor angiogenesis [10] and promoting tumor immune in ltration [14]. Our results are consistent with these previous ndings.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, ACE2 de ciency may exacerbate outcomes in patients with SARS-CoV-2 infection [27]. Indeed, a recent study showed that ACE2 was downregulated in virus-infected lung tissue [14], indicating a potential protective role of ACE2 in patients with SARS-CoV-2 infection. Thus, using ACE2 inhibitors for preventing and treating SARS-CoV-2 infections may not be an advisable strategy for individuals with hypertension, heart disease, or cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the susceptibility of endometrial tissue to COVID-19 has not been con rmed in the clinical setting (14). Studying large databases has shown that the uterine corpus endometrial carcinoma tissue is more susceptible to SARS-CoV-2 infection, which also affected the tumor prognosis after COVID-19 infection (27). Other cancer types, including gastrointestinal and urinary tract tumors have also shown higher susceptibility to COVID-19 infection, attributed to the expression of ACE 2 and TMPRSS2 in cancer tissues (22,28).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, correlations between prognostic biomarker expression and gene markers of tumor-infiltrating immune cells were further explored using Spearman’s correlation. Gene markers have been reported in previous studies [ 20 ].…”
Section: Methodsmentioning
confidence: 99%